Desain dan Pengembangan Aplikasi Sistem Informasi Administrasi Desa - Irawan, Paulus Lucky Tirma; Kurniawan, Yudhi; Swastika, Windra (Jurnal SOLMA, 2019)
Tegalweru is located in Dau, Malang. Tegalweru has 3 hamlets, including Krajan, Kraguman and Jengglong hamlet. In data management, Tegalweru is assisted by a number of village officials consisting of Kaur (Head of General Affairs), Finance Chief, Kebayan, Kuwono, Modin, Pramu, Kepetengan and Kamituwo. One routine administration that is directly related to community service is correspondence activities, such as making certificates starting from the domicile certificate, business domicile certificate, residence certificate, and others. Based on the initial analysis of the findings in the field, there are several potential problems found. The absence of a system makes the administrative routine management process less effective because population data that is the main supporting data must be accessed manually. This problem needs to get special attention so that Tegalweru can minimize the mistakes that occur due to the administrative process carried out manually services to the community can be improved.